Gender bias and the intrahousehold distribution of resources: Evidence from African nuclear households in South Africa - Olivier Bargain; Prudence Kwenda-Magejo; Miracle Ntuli (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper applies recent developments in collective model estimation to elicit the household resource sharing rule, i.e. the amount of household resources accruing to fathers, mothers, and their children among African families in South Africa. We use the 2010/11 South African Income and Expenditure Survey as it contains exclusive goods, i.e. goods consumed by specific household members, to be used for identification. We rely on a collective model of household consumption that accounts for (potentially unequal) resource sharing and jointness in consumption (generating economies of scale). Results indicate that men tend to receive more than women (even if imprecise estimates make the difference statistically insignificant) and there is a sharp gender differential in terms of poverty. Ignoring economies of scale leads to an overestimation of poverty among adult men and women living with others. Children's resource shares are in line with international standards but household resources are relatively low among African families so that ignoring intrahousehold allocation leads to an underestimation of child poverty.
Keywords: D11; D12; D3; I31; J12; 330; collective model; sharing rule; economies of scale; individual poverty; South Africa